Frequency of the allelic variant (Trp8Arg/Ile15Thr) of the luteinizing hormone gene in a Brazilian cohort of healthy subjects and in patients with hypogonadotropic hypogonadism (Clinics, 2005)
PURPOSE: To evaluate the frequency of allelic variant Trp8Arg/Ile15Thr in the luteinizing hormone beta-subunit gene in a Brazilian population of healthy subjects and in patients with hypogonadotropic hypogonadism. SUBJECTS AND METHODS: Two hundred and two adults (115 women) with normal sexual function and 48 patients (24 women) with hypogonadotropic hypogonadism underwent a molecular study of the the luteinizing hormone beta-subunit gene using a polymerase chain reaction technique followed by enzymatic digestion with the restriction enzymes Nco I (for detection of the Trp8Arg point mutation) and Fok I (for detection of the Ile15Thr point mutation). Basal luteinizing hormone and FSH, testosterone, or estradiol levels were measured in 37 healthy subjects (21 women) and in 27 hypogonadotropic hypogonadism patients (13 women) by immunofluorometric methods (hLH-Spec and hFSH-Spec, AutoDELFIA, Wallac Oy, Turku, Finland). RESULTS: The genetic variant of the luteinizing hormone beta-subunit gene was present at a similar frequency in healthy subjects (14.4%) compared to patients with hypogonadotropic hypogonadism (16.6%). There was no effect of the allelic variant of the luteinizing hormone beta-subunit gene on luteinizing hormone levels in patients with hypogonadotropic hypogonadism as compared to healthy subjects. CONCLUSION: This study indicates that the allelic variant Trp8Arg/Ile15Thr of the luteinizing hormone beta-subunit gene is a common polymorphism in the Brazilian population (14.4%). The same frequency of this luteinizing hormone variant in the groups with hypogonadotropic hypogonadism and in the healthy subjects excludes a relationship between this variant and hypogonadotropic hypogonadism.